BRANDING UMKM TAPE PAK LAN MELALUI PEMBUATAN LOGO STIKER DI DUSUN SEMEN, MUSIR KIDUL - Nina Zenitha Sekar Sari; Rahman Amrullah Suwaidi (EDUPEDIA Publisher, 2023)
Strict business competition requires that each business must implement a strategy in product marketing to gain competitive advantage. One of the strategies to increase purchasing interest in consumers is the application of branding to products. Branding is the activity of creating images on a product. MSMEs Tape Pak Lan is one of the MSMEs located in Semen Musir Kidul hamlet. Although it has been standing for quite a long time, this MSMMEs do not have a logo on their business at all. Looking at the problem, this devotion activity aims to create a visual identity on MSMMEs Tape Pak Lan through the logo branding process. The creation of the logo is considered appropriate because it is in accordance with the business conditions required by MSMM Tape Pak Lan. The method carried out in this service is to start by conducting a survey on MSMEs Tape Pak Lan by conducting interviews, analysis of business needs, and submission of logo results. The result of this devotion is the existence of a visual identity through the logo for tape product packaging.